The effect of firm-specific and macroeconomic uncertainty on firm leverage, short-term and long-term debt in the Philippines - Chow, Yee Peng; Junaina Muhammad; A. N. Bany-Ariffin; Cheng, Fan Fah (Penerbit Universiti Kebangsaan Malaysia, 2019)
Firms often face uncertainties which may affect corporate financing decisions. As uncertainty has potential adverse and destabilizing effects on firms, this study is carried out to examine the influence of firm-specific and macroeconomic uncertainty on firm leverage, short-term and long-term debt. Based on a panel of Philippine listed firms from 2004-2014, we adopt a dynamic panel data estimation technique, namely the Generalized Method of Moments to conduct our analyses. The results provide strong evidence of the adverse influence of firm-specific and macroeconomic uncertainty on leverage. Furthermore, the results indicate that while short-term debt is adversely impacted by firm-specific and macroeconomic uncertainty, long-term debt is merely influenced by macroeconomic uncertainty. This implies that although Philippine firms consider firm-specific and macroeconomic uncertainty in their short-run financing decisions, they are primarily concerned about macroeconomic uncertainty in the long-run. This paper addresses the paucity of research that has been conducted in this area, particularly in the context of developing countries. The findings provide important insights into the way firms derive their short- and long-run corporate financing decisions when encountering uncertainties. The insights can guide policymakers to formulate suitable policies to ensure stability in the business and macroeconomic environment.